THE FUSION EFFECT OF COMPUTED RADIOGRAPHY IMAGE OF WELDING PLATE DIFFERENT IN POWER TO ITS IMAGE QUALITY - Yoshandi, Tengku Mohammad (Journal of Renewable Energy and Mechanics, 2020)
Instrument testing which is done is indutries are one of method to maintain the primary condition of insrument with purpose to prevent damage on instrument which will cause accident of death. Testing conducted using non-destructive technique or NDT, which is one of testing which not leave any damage or harm to the test speciment. Non-destructive testing in industry is levelling up to digital display. This digital radiography using image plate instead of film. In this research, computed radiography invarious energy and curent is used. Voltage and current are factors that give effect to the resulting image. Voltage give effect to contrast, contrast increase the number of x-ray emmit from the x-ray tube, which is higher the current make the noise higher to image. In this study, the important parameters are voltage and current. Exposure distant and time are 100 cm and 1 minute. With these distant and time, the speciment which 17 mm thick being exposed to the radiation with various energy and current which is 160 kV, 180 kV, and 200 kV, 3 mA, 5 mA, and 10 mA. The resulting images are analyzed with iSee! and image fusion using MATLAB. Simple fusion method is the simplest way of fusing the image which done by the pixel selection, or with extraction. Image that been fused divided by two, which is the fused image with the same voltage but different current and vice versa. The comparison is done by determined the SNR in image with iSee!. After fusion, the SNR is increase which mean the increase of image quality